DAMPAK MERGER BANK SYARIAH INDONESIA TERHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY - Nugroho, Sigit; Juliarto, Agung (Diponegoro Journal of Accounting, 2024)
This research aims to examine the impact of Indonesian sharia bank mergers on abnormal returns and Trading Volume Activity in the Indonesian sharia stock index. The study covers a period of 15 days before and 15 days after the merger. The research method used is purposive sampling approach with sample selection criteria based on Islamic banking stocks owned by state-owned enterprises (BUMN) that underwent merger activities from 2020 to 2022. Secondary data was obtained from yahoofinance with the issuer codes BRIS and JKSE. Data analysis was conducted through descriptive statistical analysis. The research results show changes in abnormal returns and Trading Volume Activity after the merger. The conclusion of this research is that the merger of Indonesian sharia banks does not have a significant impact on abnormal stock returns and Trading Volume Activity (TVA) of Bank Syariah Indonesia.